Chapter 8 Ageism in the Third Age (2018)
In the developed world, later life has brought more opportunities to contribute to society and pursue personal goals outside the role of paid work, combined with less stigma and greater recognition of the worth of older people. These values do not necessarily extend to the “oldest old” where some people in the fourth age (people 80 years old and over) continue to face increasing stigma and societal stereotypes from those in the third age (people 60–79 years old). Ageism between these two cohorts is rarely discussed in the literature. Potential ageism involves stereotypical perceptions of the oldest old and may prove detrimental to those transitioning from the third to the fourth age if a resultant resistance to maintain their engagement and independence into older age occurs. This chapter explores the subtleties of these inter-cohort ageist discourses particularly from a health and social care perspective and considers the implications for transitions of older people between the third and fourth age. It addresses the challenges and adjustments needed to ensure continuing and inclusive engagement in society, in order to support independence to grow old without the fear of discrimination.